Systemic Challenges in Internship Training for Health-Service Psychology: A Call to Action From Trainee Stakeholders. (September 2022) - Palitsky, R.; Kaplan, D. M.; Brodt, M. A.; Anderson, M. R.; Athey, A.; Coffino, J. A.; Egbert, A.; Hallowell, E. S.; Han, G. T.; Hartmann, M.-A.; Herbitter, C.; Herrera Legon, M.; et al.
The challenges observed in health-service-psychology (HSP) training during COVID-19 revealed systemic and philosophical issues that preexisted the pandemic but became more visible during the global health crisis. In a position article written by 23 trainees across different sites and training specializations, we use lessons learned from COVID-19 as a touchstone for a call to action in HSP training. Historically, trainee voices have been conspicuously absent from literature about clinical training. We describe long-standing dilemmas in HSP training that were exacerbated by the pandemic and will continue to require resolution after the pandemic has subsided. We make recommendations for systems-level changes that would advance equity and sustainability in HSP training. This article advances the conversation about HSP training by including the perspective of trainees as essential stakeholders.